Kontribusi Pemikiran Aristoteles tentang Retorika terhadap Pengajaran Mahārah Kalām di Perguruan Tinggi - AHMAD NIHAMI MUNAWIR; KAMAL YUSUF (Sekolah Tinggi Ilmu Tarbiyah Al-Hilal Sigli Aceh- Indonesia, 2025)
Rhetoric as the art of effective speaking has received considerable attention since Ancient Greece, particularly through the writings of Aristotle. In his work Rhetorica, Aristotle emphasizes three main aspects of persuasion, namely ethos (the credibility of the speaker), pathos (emotional appeal), and logos (the power of logic and argumentation). These three concepts have significant relevance in the context of teaching mahārah kalām (speaking skills) in higher education, especially in Arabic language learning. Mahārah kalām requires not only the ability to express words linguistically correctly, but also the skills to construct arguments, convince audiences, and adapt speaking styles to social and academic contexts. Through the integration of Aristotle's rhetorical principles, students can be trained to develop more comprehensive communication skills, including clarity of ideas, logical strength, and effective delivery. This study confirms that the teaching of mahārah kalām in higher education can be improved by adapting classical rhetoric theory as a pedagogical foundation that complements modern learning methods. Thus, Aristotle's thinking is not only relevant in Western philosophical tradition, but can also make a real contribution to the development of critical, logical, and persuasive Arabic language skills.